The Evaluation of Implementation of Agricultural Sustainable Development Policy in the European Union - Julian Krzyżanowski (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Author tries to evaluate two elements of implementation of agricultural sustainable development policy in the European Union. Those elements are: “greening” and European innovation partnership. Greening is carried out by: crop diversification, maintenance of permanent grassland (PG), maintenance of ecological focus areas (EFA). Diversification of crops was carried out for three fourth of areas of arable lands in the EU. Diversification prevents soil erosion. Share of PG in the overall area of agricultural land in the EU is 29 %. The highest indicator is at present in the United Kingdom (90%), and the lowest in Cyprus, Malta, Denmark and Finland. From the set of actions maintaining the pro-environmental areas (EFA), the most popular were: setting aside (27 member states), and the least popular – afforestation (only 11 countries). When it comes to EFA area, the biggest share was the area for legume plants. New pro-environmental instrument is European Innovation Partnership for productive and sustainable agriculture. There has already been some results of this action in the EU countries.